2021
DOI: 10.3390/antiox11010044
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Glutamine Inclusion Regulates Immune and Antioxidant System, as Well as Programmed Cell Death in Fish to Protect against Flavobacterium columnare Infection

Abstract: The susceptibility of animals to pathogenic infection is significantly affected by nutritional status. The present study took yellow catfish (Pelteobagrus fulvidraco) as a model to test the hypothesis that the protective roles of glutamine during bacterial infection are largely related to its regulation on the immune and antioxidant system, apoptosis and autophagy. Dietary glutamine supplementation significantly improved fish growth performance and feed utilization. After a challenge with Flavobacterium column… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 102 publications
(107 reference statements)
0
2
0
Order By: Relevance
“…Jian) (Hu, et al, 2015;Liu, et al, 2015;Silva, et al, 2010). Glutamate has been demonstrated to reduce intestinal in ammation and protect intestinal epithelial cells from oxidative stress in studies on yellow cat sh (Jiao, et al, 2021) and Jian carp (Chen, et al, 2009). These ndings support the use of glutamine in aquatic animals to improve growth performance and intestinal structure.…”
Section: Introductionmentioning
confidence: 76%
“…Jian) (Hu, et al, 2015;Liu, et al, 2015;Silva, et al, 2010). Glutamate has been demonstrated to reduce intestinal in ammation and protect intestinal epithelial cells from oxidative stress in studies on yellow cat sh (Jiao, et al, 2021) and Jian carp (Chen, et al, 2009). These ndings support the use of glutamine in aquatic animals to improve growth performance and intestinal structure.…”
Section: Introductionmentioning
confidence: 76%
“…Further, the work of Xu et al focused on docosahexaenoic acid (DHA), as a nutritional modulator, to alleviate palmitic-acid-induced inflammation of macrophages via the TLR22-MAPK-PPAR/Nrf2 pathway in large yellow croakers, thereby improving the utilization rate of palm oil in aquafeed [ 11 ]. Another study found that dietary glutamine could regulate immune and antioxidant capacity to protect against Flavobacterium columnare infection in yellow catfish [ 12 ]. The authors suggest their study firstly demonstrated the regulatory roles of glutamine in the fish immune and antioxidant system and reported its inhibitory effects on fish apoptosis and autophagy during pathogenic infection.…”
mentioning
confidence: 99%